MRI-Based Radiomics Models for Predicting Risk Classification of Gastrointestinal Stromal Tumors - Mao, Haijia; Zhang, Bingqian; Zou, Mingyue; Huang, Yanan; Yang, Liming; Wang, Cheng; Pang, PeiPei; Zhao, Zhenhua (Frontiers in Oncology, 2021)
Background We conduct a study in developing and validating four MRI-based radiomics models to preoperatively predict the risk classification of gastrointestinal stromal tumors (GISTs). Methods Forty-one patients (low-risk = 17, intermediate-risk = 13, high-risk = 11) underwent MRI before surgery between September 2013 and March 2019 in this retrospective study. The Kruskal–Wallis test with Bonferonni correction and variance threshold was used to select appropriate features, and the Random Forest model (three classification model) was used to select features among the high-risk, intermediate-risk, and low-risk of GISTs. Receiver operating characteristic (ROC) curves were generated based on radiomics features. Area under the curve (AUC), accuracy, sensitivity, and specificity for risk classification were reported. Linear discriminant analysis (LDA) was used to assess the discriminative ability of these radiomics models. Results The high-risk, intermediate-risk, and low-risk of GISTs were well classified by radiomics models, the micro-average of ROC curves was 0.86, 0.78, 0.85 and 0.92 for T1WI, T2WI, ADC and combined three MR sequences. And ROC curves achieved excellent AUCs for T1WI (0.86, 0.72 and 0.79), T2WI (0.66, 0.75 and 0.74), ADC (0.82, 0.86 and 0.78) and combined three MR sequences (0.95, 0.86, 0.78) for the diagnosis of high-risk, intermediate-risk, and low-risk of GISTs, respectively. In addition, LDA demonstrated the different risk of GISTs were correctly classified by radiomics analysis (61.0% for T1WI, 73.2% for T2WI, 83.3% for ADC, and 82.9% for the combined three MR sequences). Conclusions Radiomics models based on a single sequence and combined three MR sequences can be a noninvasive method to evaluate the risk classification of GISTs, which may help the treatment of GISTs patients in the future.